Mapping Cerrado remnants in an anthropized landscape in southeast Brazil - Cima, Isabela Silva [UNESP]; Amaral, Silvana; Massi, Klécia Gili [UNESP] (Elsevier, 2023)
In the eastern São Paulo state, Brazil, a disjoint tropical savanna (Cerrado) site occurs in Vale do Paraíba Paulista. Considering the degradation of Cerrado in the region and that currently LULC mapping is not accurate enough to properly map Cerrado vegetation in an anthropized landscape, we aimed to locate Cerrado remnants in the region and to evaluate the conservation status of these remnants and its main anthropic pressures. We hypothesized that Cerrado pacthes in Vale do Paraíba Paulista were small, irregular in shape, disconnected from each other, and threatened by agriculture and urban expansion, which we found. We also expected that woody formations of Cerrado would predominate in the region, what we observed. Different Cerrado formations covered an area of 3153.35 ha in Vale do Paraíba Paulista, only about 1.5% of original extension, and remnants located within private properties. This study highlighted Cerrado occurrence in Vale do Paraíba Paulista and the need for conservation public policies for this biome in the region.
Keywords: Brazilian savannah; Cerrado conservation; Cerrado remnants; Land use and cover; Landscape metrics